1993
DOI: 10.1016/0014-5793(93)80205-9
|View full text |Cite
|
Sign up to set email alerts
|

The complete amino acid sequence of a thrombin‐like enzyme/gyroxin analogue from venom of the bushmaster snake (Lachesis muta muta)

Abstract: The complete amino acid sequence of a thrombin-like enzyme with gyroxin activity isolated from the venom of the bushmaster snake La&e& mutu muta was determined by automated and DABITWPITC microsequencing of the intact protein; fragments derived from it by separate cleavages with cyanogen bromide, iodosobenzoic acid and hydroxylamine; and peptides resulting from enzymatic digestions with trypsin, pepsin, chymotrypsin, and elastase. The protein, which is composed of 228 residues, contains four putative sites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…The homology study (Figure 4) showed that Rhombeobin shared a high degree of sequence identity with SVSP with thrombin-like activity [12, 13, 1518, 28, 35] especially with LM-TL ( Lachesis muta muta ). Detailed analysis showed small but important differences between Rhombeobin and LM-TL.…”
Section: Discussionmentioning
confidence: 99%
“…The homology study (Figure 4) showed that Rhombeobin shared a high degree of sequence identity with SVSP with thrombin-like activity [12, 13, 1518, 28, 35] especially with LM-TL ( Lachesis muta muta ). Detailed analysis showed small but important differences between Rhombeobin and LM-TL.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has accumulated in our lab that has allowed us to safely presume that the 45-47 kDa species isolated from L. m. rhombeata venom using chromatography on Am-PABA resin is virtually identical to the ortologue from L. m. muta venom that had it primary structure determined [36,45]. In fact, the very existence of these subspecies seems not to be a consensus among herpetologists [46].…”
Section: Computer-aided Evaluation Of the Interaction Between Lmm-tlementioning
confidence: 99%
“…For the ligand representing Table 2 Comparison of inhibition constants (K i ) of S1-directed inhibitors of thrombin-like serine proteases (TLSPs) from Bothrops jararacussu (BJ-48) and Lachesis muta muta (Lmm-TLE) venoms S1-directed inhibitor b Constants at 25 • C using BapNA as substrate [45]. Values are shown as means ± standard deviations.…”
Section: Computer-aided Evaluation Of the Interaction Between Lmm-tlementioning
confidence: 99%
“…The enzyme is a single polypeptide chain glycoprotein with Mr of 33 kDa, and belongs to the trypsin family of serine proteinases. The partial amino acid sequence (77%) of the enzyme reveals that it shares structural homology with other serine proteinases isolated from the same source including the plasminogen activator (LV-PA) (15) and the clotting enzyme (16) as well as with other serine proteinases from snake venoms and mammalian kallikrein (8,17).…”
Section: Introductionmentioning
confidence: 99%